2006
DOI: 10.1063/1.2408648
|View full text |Cite
|
Sign up to set email alerts
|

Large photocurrent generation in multiwall carbon nanotubes

Abstract: The authors demonstrate the ability of multiwall carbon nanotubes to generate photocurrents in the near ultraviolet and visible spectral ranges using electrochemical photocurrent measurements. The photogenerated current depends on the excitation wavelength similar to that for single wall carbon nanotubes. Its intensity and modulation can be related to the carbon nanotubes morphology. The maximum photon-to-current conversion efficiency is approximately 7%, about 50 times higher than that reported for single wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 19 publications
9
50
1
Order By: Relevance
“…This can be ascribed to structural fluctuations in the CNT that influenced the optical response, as we have already reported. 18 A similar trend in the IPCE curves has been obtained from the MWCNT samples decorated with Ag and Cu, Figs. 2(b) and 3(c), respectively.…”
supporting
confidence: 61%
“…This can be ascribed to structural fluctuations in the CNT that influenced the optical response, as we have already reported. 18 A similar trend in the IPCE curves has been obtained from the MWCNT samples decorated with Ag and Cu, Figs. 2(b) and 3(c), respectively.…”
supporting
confidence: 61%
“…Firstly there has been some evidence that carbon nanotubes can replace platinum as a catalyst because of their high surface area and electronic properties [6][7][8]. However, these SWCNTs are also of interest because they can also act as photosensitive elements themselves [9][10][11][12]. Light response of the cell is measured by measuring current-voltage response (I-V curves) under illumination.…”
Section: Introductionmentioning
confidence: 99%
“…A photoelectric conversion efficiency of about 6.2% has been achieved for the DSC with a CNT-sponge CE, compared with the 7.6% of that with Pt CEs. Recently, our research group showed that 2D films made of MWCNTs only can be used as optical active medium for light energy conversion in a solar cell device [16]. Similarly, we performed a similar measurement using a piece of CNT-sponge, which possesses a self-sustainable structure, as a working electrode in standard electrochemical cell.…”
Section: Objectives Approach and Resultsmentioning
confidence: 88%
“…Similarly, we performed a similar measurement using a piece of CNT-sponge, which possesses a self-sustainable structure, as a working electrode in standard electrochemical cell. The photo-response was measured as a function of the incident photon wavelength and expressed in terms of quantum efficiency (IPCE) [16], as reported in Figure 6. In the same figure the response obtained from a MWCNT film grown on a silicon substrate [16] is reported for comparison.…”
Section: Objectives Approach and Resultsmentioning
confidence: 99%
See 1 more Smart Citation